Interactions between voluntary and stimulus-driven spatial attention mechanisms across sensory modalities. - Santangelo, V; Olivetti Belardinelli, M; Spence, C; Macaluso, E (2009)
In everyday life, the allocation of spatial attention typically entails the interplay between voluntary (endogenous) and stimulus-driven (exogenous) attention. Furthermore, stimuli in different sensory modalities can jointly influence the direction of spatial attention, due to the existence of cross-sensory links in attentional control. Using fMRI, we examined the physiological basis of these interactions. We induced exogenous shifts of auditory spatial attention while participants engaged in an endogenous visuospatial cueing task. Participants discriminated visual targets in the left or right hemifield. A central visual cue preceded the visual targets, predicting the target location on 75% of the trials (endogenous visual attention). In the interval between the endogenous cue and the visual target, task-irrelevant nonpredictive auditory stimuli were briefly presented either in the left or right hemifield (exogenous auditory attention). Consistent with previous unisensory visual studies, activation of the ventral fronto-parietal attentional network was observed when the visual targets were presented at the uncued side (endogenous invalid trials, requiring visuospatial reorienting), as compared with validly cued targets. Critically, we found that the side of the task-irrelevant auditory stimulus modulated these activations, reducing spatial reorienting effects when the auditory stimulus was presented on the same side as the upcoming (invalid) visual target. These results demonstrate that multisensory mechanisms of attentional control can integrate endogenous and exogenous spatial information, jointly determining attentional orienting toward the most relevant spatial location.